Advances in Biochemical Engineering/Biotechnology
DOI: 10.1007/10_2007_060
|View full text |Cite
|
Sign up to set email alerts
|

Zymomonas mobilis for Fuel Ethanol and Higher Value Products

Abstract: High oil prices, increasing focus on renewable carbohydrate-based feedstocks for fuels and chemicals, and the recent publication of its genome sequence, have provided continuing stimulus for studies on Zymomonas mobilis. However, despite its apparent advantages of higher yields and faster specific rates when compared to yeasts, no commercial scale fermentations currently exist which use Z. mobilis for the manufacture of fuel ethanol. This may change with the recent announcement of a Dupont/Broin partnership to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
111
0
6

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 99 publications
3
111
0
6
Order By: Relevance
“…However, engineered bacteria such as Escherichia coli, Zymomonas mobilis, and others are also being developed and deployed in search of superior production economics (2 and 10). Z. mobilis are Gram-negative facultative anaerobic bacteria with desirable industrial biocatalyst characteristics, such as high-specific productivity, high ethanol yield, and ethanol tolerance (12% v∕v) (10)(11)(12). The genome sequence of Z. mobilis strain ZM4 has been determined (13) and its annotation improved by our group recently (14).…”
mentioning
confidence: 99%
“…However, engineered bacteria such as Escherichia coli, Zymomonas mobilis, and others are also being developed and deployed in search of superior production economics (2 and 10). Z. mobilis are Gram-negative facultative anaerobic bacteria with desirable industrial biocatalyst characteristics, such as high-specific productivity, high ethanol yield, and ethanol tolerance (12% v∕v) (10)(11)(12). The genome sequence of Z. mobilis strain ZM4 has been determined (13) and its annotation improved by our group recently (14).…”
mentioning
confidence: 99%
“…Among many microorganisms that have been exploited for ethanol production, Saccharomyces cerevisiae still remains the most widely used [1]. However, Zymomonas mobilis has been the object of considerable interest in the past decades because of its ability to ferment hexoses into ethanol rapidly and efficiently [3]. Despite this, wild Z. mobilis strains cannot use xylose, the major component of hemicellulose [4].…”
mentioning
confidence: 99%
“…Z. mobilis is a type of bacteria which has an ethanol-tolerant characteristic, therefore it has the higher level of glucose uptake and able to produce ethanol in anaerobic conditions. In addition, these bacteria also have the ability to increase the ethanol purity (Rogers et al, 2007). Furthermore, Choi et al (2008) showed a great potential of this microorganism for conversion of industrial starch feedstock such as rice, barley, and cassava to produce bioethanol.…”
Section: Introductionmentioning
confidence: 99%